Evaluation of Knwledge of Epileptic Patients about Their Disorder - Sheida Sha'afi (University of Social Welfare and Rehabilitation Sciences, 2001)
Objective: Patients' knowledge of their disorder is an essential component of their care. Studies about this issue are scanty. We report the first study in Iranian epileptic patients from the Epilepsy clinic. Materials & Methods: Seven hundred and fifty patients above 15 yr. old were selected. EPKQ (Epilepsy patients' knowledge Questionnaire) of Ohio University is used for gathering of information. This questionnaire included demographic data-topics related seizure definition-type and dose of drugs-legal issues of driving and employment. Then information was analyzed statistically with EP16 software. Results: Of 750 patients (280 female, 470 male) the average age and number with epilepsy were 32±10 and 12±10 years respectively. Neither age nor number of years with epilepsy correlated with scores. Years of education & sexuality (male' scores were higher) affected scores significantly. Twenty percent believed that epilepsy is a mental disorder. Thirty-eight percent knew which factors increases seizures. The lowest scores pertained to antiepileptic drug side effects and discontinue of them (only 5% knew enough). Overall patients' knowledge level was low. Conclusion: Patients with epilepsy are not knowledgeable about their disease. This causes increase of injuries during attacks, problems of treatment and finally affects quality of their lives. There is a need for educational intervention in this population. Particularly about antiepileptic drugs side effects (AED), proper time of AED discontinuation and legal issues of epilepsy.